The social foundations of (in)effective states: Uttar Pradesh's response to the COVID-19 pandemic - Indrajit Roy (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
A rich and growing literature illustrates the paradox of COVID-19 responses by governments across the world. States with higher levels of authority and capacity have struggled to respond effectively to COVID-19, while states with low capacity and authority have been more effective in containing the pandemic. Subnational comparisons within India appear to support this worldwide finding, illustrated by the official data on pandemic management presented by the Indian state of Uttar Pradesh. Against such appearances, this paper questions the official presentation of the Uttar Pradesh data. Based on reportage from grassroots sources, this paper argues that Uttar Pradesh witnessed a significant extent of undercounting. However, the paper cautions against assumptions that undercounting of COVID cases and deaths in the state reflects poor state capacity. Quite to the contrary, the paper situates the growing capacity of the state in Uttar Pradesh within its historical context to suggest it improved legitimacy and authority as it transitioned from an 'elitist social coalition' between 1947 and 1989 to an 'inclusive social coalition' from 1989 to 2017. The poor management of the pandemic by the present government of the state cannot thus be attributed to factors such as weak state capacity, poor authority, or limited legitimacy. What explains this paradox of poor COVID management despite improved state effectiveness? This paper reflects on this paradox by highlighting the ideational commitment of the state government to crafting an 'ethnic social coalition' rather than responding to the social welfare needs of the population.
Keywords: I38; 330; Uttar Pradesh; COVID-19; elitist social coalition; inclusive social coalition; ethnic social coalition; state effectiveness